Experiences of adolescents with type I diabetes mellitus Yucatan state. A phenomenological perspective - López Osorio , Argelia Lizandra (Consorcio de Universidades Mexicanas A.C., 2016)
Diabetes is a disease that has increased in prevalence in recent years and is considered one of the major global health problems (Martinez Chamorro, Luzuriaga Lastra Martinez, &Thomas, 2002). Adolescents with diabetes appear to be red flags among people with diabetes, since, s well as working their adaptation and acceptance of the disease, it is necessary to do it with the changes that occur due to their stage of development. This study aims to describe the life experiences of adolescents with diabetes mellitus type I of a civil association of Yucatan state; from their own narratives and stories and from the voice of related actors. Contextualization was carried out through a phenomenology, using techniques participatory workshops, group interviews unstructured and semi-structured individual interviews. They involved 16 young people with type I diabetes mellitus, of which 9 are men and 7 are women, whose ages are between 13 and 17; 6 parents, 2 men and 4 women; civil staff and staff Health Association works as an external consultant. It was observed that the different actors relate similar aspects of a psychological nature. However, they highlight the speeches of adolescents, which reflect the saturation power, medical power that tells them how regulated, parents who insist on a strong care and a society that states and rejects their living conditions.